PENGETAHUAN, SIKAP DAN PERILAKU PENCEGAHAN COVID-19 PADA REMAJA SEBAGAI UPAYA MEMUTUS RANTAI PENYEBARAN COVID 19 DI KABUPATEN CIANJUR - Ambar Dani syuhada; Akmal, Dzul; Mardiana, Hasna; Dewita, Trisna (JURNAL KESEHATAN KARTIKA, 2021)
ABSTRACT Background: COVID-19 is transmitted through human-to-human transmission through droplets, direct contact and has an incubation period of 2-14 days. The lack of effective preventive measures to flatten the curve of COVID-19 cases can be seen from the lack of discipline of the community towards the protocol set by the government. The implementation of preventive measures is mostly caused by behavioral problems that are often determined by knowledge and attitudes, especially to prevent transmission to the school cluster. The method used in this study is cross-sectional a web-based and data collection using the online platform Google Form. The population in this study were adolescents grade VIII SMP Negeri 1 Cugenang, Cianjur Regency. Sampling was done by using a stratified random sampling technique which obtained 34 respondents. Correlation test using Square-Test. The measuring instrument used was a questionnaire to measure knowledge, attitudes, gender, place of residence, and COVID-19 prevention behavior. The results of this study indicate that the factors associated with COVID-19 prevention behavior are the factors of knowledge (p = 0.002), attitude (p = 0.022), and place of residence (p = 0.007). This study suggests providing education as a long-term strategy to increase knowledge and reduce negative attitudes towards COVID-19, especially among adolescents. Use of social media and electronic media as a means of health education